Development of a Sukuraga Wayang Scrapbook to Improve Elementary School Students’ Reading Comprehension Skills - Imelda Mauludy S; Iis Nurasiah; Arsyi Rizqia Amalia (FKIP - Universitas Riau, 2026)
Indonesian language learning in elementary schools still faces challenges in reading comprehension. Many students have difficulty understanding texts, identifying main ideas, and interpreting messages. In addition, limited use of engaging learning media contributes to low interest and participation in reading activities. This study aimed to develop a Sukuraga Wayang scrapbook medium and determine its feasibility and effectiveness in improving elementary school students’ reading comprehension skills. The scrapbook integrates Sukuraga Wayang illustrations, reading texts, contextual learning activities, and QR code-based audio narration in an interactive visual format. It also incorporates local wisdom through Sukuraga Wayang characters and presents stories related to students’ daily lives, making learning more meaningful and engaging. The study employed the Research and Development (R&D) method using the ADDIE model. Data were collected through interviews, observations, validation questionnaires, student response questionnaires, and pretest-posttest assessments. Data were analyzed using feasibility testing, paired sample t-tests, and N-gain analysis. The results showed that the Sukuraga Wayang scrapbook was highly feasible based on expert and practitioner evaluations. The effectiveness test revealed a significant difference between pretest and posttest scores (Sig. < 0.05). Students’ average scores increased from 58.89 to 87.22, while the N-gain indicated a moderate improvement in reading comprehension skills.